Synopsis of the Ozyptila rauda-group (Araneae, Thomisidae), with revalidation of Ozyptila balkarica Ovtsharenko, 1979 - Marusik, Yuri M. (Zootaxa, 2008)
Ozyptila balkarica Ovtsharenko, 1979, belonging to the Holarctic Ozyptila rauda-group was thought to be a junior synonym of O. orientalis Kulczyński, 1926, because of its indistinguishable females. Comparison of topotype males from Caucasus and Kamchatka revealed clear differences in the shape of copulatory organs and carapace patterns; thus the junior name is revalidated here. Because the differences between the two taxa are of the same level as between O. orientalis and O. basegica Esyunin, 1992, which is considered a subspecies of the former species, subspecific rank to O. orientalis balkarica stat. nov. is suggested. Males of the two subspecies are illustrated, and a synopsis of the whole O. rauda-group accounting 14 species and subspecies is given. O. sedotmikha Levy, 2007, from Israel was found to belong to this group. Distribution of all species is mapped.